ANALISIS PENERAPAN PEMUNGUTAN PAJAK PERTAMBAHAN NILAI PADA BUMN SEBAGAI PEMUNGUT DAN TIDAK SEBAGAI PEMUNGUT PAJAK PERTAMBAHAN NILAI - Aksari, Agista Ayu (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2017)
On 1st July 2012 SOE (State-Owned Enterprises)become the Value Added Tax (VAT) collector. According to the regulation of the Ministher of Finance No.85/PMK.03/2012 about the appointment of the State Owned Enterprises to collect, deposit and reporting Value Added Tax (VAT) and Sales Tax on Luxurious Goods, and precedures for collecting, depositing and reporting. The purpose of this research is to determine the difference between SOE as a Value Added Tax collector and not as a Value Added Tax collector.The object of this research is PT Pelabuhan Indonesia III cabang Benoa. The data analysis in this research is to analyze the calculation and reportig of VAT before being VAT collector and when it became VAT collector.The result of this research it is known that are the application of the value added tax on PT Pelabuhan Indonesia III Cabang Benoa before becoming tax collector is charged directly by fiskus and has official assessment system and as a PT Pelabuhan Indonesia III Cabang Benoa has a self assessment system whereby PT Pelabuahan Indonesia III Cabang Benoa became ILL wapu. Differnce in PT Pelabuhan Indonesia III Cabang Benoa as a collector, and the collector Is a time before becoming a collector has aself just my assessment system whereas before becoming a collector has official assessment system. Tax eceipt when it became a collector of VAT using duplicate counts 3 before becoming a collector only uses 2 of the double. For SSp before becoming a duplicate while using 4 collector as a collector to use duplicate.